Penerapan Teknik Bagi Unsur Langsung (BUL) pada Identifikasi Afiks Bahasa Dayak Benuaq - Widyatmike Gede Mulawarman; Yeri Iswanto (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2018)
This study aims to describe the form, function, and meaning of affix attached to the basic form of Benuaq language in Kampung Jengan Danum, Damai District, West Kutai Regency. This research is qualitative research with the technique of data analysis is BUL (Bagi Unsur Langsung) technique. This study was conducted in Kampung Jengan Danum, Damai District, West Kutai Regency. The research data is the entire word affixed spoken of native speakers Benuaq Kampung Jengan Danum. Data collection techniques used are recording techniques, cakap libat semuka technique, and simak cakap technique. The results showed that the Dayak Benuaq language in Kampung Jengan Danum has three forms affix, that is prefixes, suffixes, and combination of affixes. The prefixes are: {be-}, {pe-}, {peN-}, {te-}, and N-. The suffixes are: {tn}. The combination of affixes are: {ke- + N-} and {sek + N-}. The affix converts the categories of adjectives into verbs, verbs into adjectives, nouns into verbs, and nouns into adjectives. The meaning of the affixation of the Benuaq Dayak’s basic word is to declare an action, result of, a job, and to say to do work.